Controlling System as a Key Factor Energy Management of an Industrial Enterprise - Shatalova, Tatyana N.; Chebykina, Marina V.; Zhirnova, Tatyana V.; Bobkova, Elena Yu. (International Review of Management and Marketing, 2016)
In this article the methodological elements of the energy management of an industrial enterprise; reveal the organizational aspects of the formation of industrial plants for energy management, energy auditing and controlling; the proposed organizational and functional structure of the analytical laboratory for energy efficiency. In order to create energy-saving systems in any enterprise in its activity it is necessary to introduce energy management, which provides an integrated approach to structural savings of various kinds of energy. Energy management from a broad perspective can be seen as an instrument of general management with a universal set of controls energy consumption and costs to obtain it. With a narrow point of view of energy management - is planned system control and accounting of energy flows in order to minimize energy costs. An important aspect of the implementation of energy management issues are consulting on energy efficiency in the work of sound methodological framework for the management of energy resources, which should be consistently implemented at two levels - technical and managerial. Keywords: energy, industry, controlling, management JEL Classifications: M11; P28